Innovations and Advances in Schistosome Stem Cell Research - You, Hong; Jones, Malcolm K.; Whitworth, Deanne J.; McManus, Donald P. (Frontiers in Immunology, 2021)
Schistosomes infect about 250 million people globally causing the devastating and persistent disease of schistosomiasis. These blood flukes have a complicated life cycle involving alternating infection of freshwater snail intermediate and definitive mammalian hosts. To survive and flourish in these diverse environments, schistosomes transition through a number of distinct life-cycle stages as a result of which they change their body plan in order to quickly adapt to each new environment. Current research suggests that stem cells, present in adults and larvae, are key in aiding schistosomes to facilitate these changes. Given the recent advances in our understanding of schistosome stem cell biology, we review the key roles that two major classes of cells play in the different life cycle stages during intramolluscan and intramammalian development; these include the germinal cells of sporocysts involved in asexual reproduction in molluscan hosts and the neoblasts of adult worms involved in sexual reproduction in human and other mammalian hosts. These studies shed considerable new light in revealing the stem cell heterogeneity driving the propagation of the schistosome life cycle. We also consider the possibility and value of establishing stem cell lines in schistosomes to advance schistosomiasis research. The availability of such self-renewable resources will provide new platforms to study stem cell behavior and regulation, and to address fundamental aspects of schistosome biology, reproductive development and survival. In turn, such studies will create new avenues to unravel individual gene function and to optimize genome-editing processes in blood flukes, which may lead to the design of novel intervention strategies for schistosomiasis.